Characterisation of Aerotolerant Forms of a Robust Chicken Colonizing Campylobacter coli - O’Kane, Peter M.; Connerton, Ian F. (Frontiers in Microbiology, 2017)
Campylobacter contaminated poultry meat is a major source of human foodborne illness. C. coli strain OR12 is a robust colonizer of chickens that was previously shown to outcompete and displace other Campylobacter strains from the chicken’s gastrointestinal tract. This strain is capable of aerobic growth on blood agar. Serial aerobic passage increased this aerotolerance as assessed by quantitative assays for growth and survival on solid media. Aerotolerance was also associated with increased peroxide stress resistance. Aerobic passage did not alter cellular morphology or motility or hinder the microaerobic growth rate. Colonization of broiler chickens by aerotolerant C. coli OR12 was significantly lower than the wild-type strain at three days after challenge but not by seven days, suggesting adaptation had occurred. Bacteria recovered from chickens had retained their aerotolerance, indicating this trait is stable. Whole genome sequencing enabled comparison with the wild-type sequence. Twenty-three point mutations were present, none of which were in genes known to affect oxidative stress resistance. Insertions or deletions caused frame shifts in several genes including, phosphoglycerate kinase and the b subunit of pyruvate carboxylase that suggest modification of central and carbohydrate metabolism in response to aerobic growth. Other genes affected include those encoding putative carbonic anhydrase, motility accessory factor, filamentous haemagglutinin, and aminoacyl dipepdidase proteins. Aerotolerance has the potential to affect environmental success and survival. Increased environmental survival outside of the host intestinal tract may allow opportunities for transmission between hosts. Resistance to oxidative stress may equate to increased virulence by virtue of reduced susceptibility to oxidative free radicals produced by host immune responses. Finally, resistance to ambient atmospheric oxygen may allow increased survival on chicken skin, and therefore constitutes an increased risk to public health.